Cannabinoids Modulate Light Signaling in ON-Sustained Retinal Ganglion Cells of the Mouse - Middleton, Terence Peter; Huang, Jin Yu; Protti, Dario Alejandro (Frontiers in Neural Circuits, 2019)
The sole output of the retina to the brain is a signal that results from the integration of excitatory and inhibitory synaptic inputs at the level of retinal ganglion cells (RGCs). Endogenous cannabinoids (eCBs) are found throughout the central nervous system where they modulate synaptic excitability. Cannabinoid receptors and their ligands have been localized to most retinal neurons in mammals, yet their impact on retinal processing is not well known. Here, we set out to investigate the role of the cannabinoid system in retinal signalling using electrophysiological recordings from ON sustained (ON-S) RGCs that displayed morphological and physiological signatures of ON alpha RGCs in dark adapted mouse retina. We studied the effect of the cannabinoid agonist WIN55212-2 and the inverse agonist AM251 on the spatial tuning of ON-S RGCs. WIN55212-2 significantly reduced their spontaneous spiking activity and responses to optimal spot size as well as altered their spatial tuning by reducing light driven excitatory and inhibitory inputs to RGCs. AM251 produced the opposite effect, increasing spontaneous spiking activity and peak response as well as increasing inhibitory and excitatory inputs. In addition, AM251 sharpened the spatial tuning of ON-S RGCs by increasing the inhibitory effect of the surround. These results demonstrate the presence of a functional cannabinergic system in the retina as well as sensitivity of ON-RGCs to cannabinoids. These results reveal a neuromodulatory system that can regulate the sensitivity and excitability of retinal synapses in a dynamic, activity dependent manner and that endocannabinoids may play a significant role in retinal processing.